Software engineering traceability method for food ingredient tracing - Azram, Nur Adila; Atan, Rodziah (IEEE, 2011)
The topic of traceability has been widely discussed in the research world. Many areas of studies have a great interest in traceability. In software engineering, traceability has been well researched and discuss especially in software development. In food industry, traceability has also been an important topic for tracing food content of various food products. In this paper, we present a software engineering traceability method for food ingredient tracing. The main goal of this research is to apply and verified that a software engineering traceability method is suitable for food ingredient tracing.